Paper-based flexible devices for energy harvesting, conversion and storage applications: A review. (April 2022) - Thakur, Anupma; Devi, Pooja
Abstract: Paper, in addition to its frequent usage in writing, packaging, printing, etc., has gained comprehensive utility as a flexible and conductive base in sensors, solar energy harvesting, conversion, and storage applications. This is due to its strategic-aiding aspect in terms of environmental friendliness, cost-effectiveness, recyclability, thin, flexible and lightweight nature, biocompatibility, etc., required to develop next-generation flexible devices. The signs of progress in paper-based devices are seen in matured technologies of the paper-based sensor for varied sectors. Also, there have been wide-ranging research efforts on developing paper-based high-performance energy harvesting, conversion, and storage solutions. However, it is a newly emerging area and needs a fundamental and state-of-the-art understanding for future devices development. Thus, the current review summarizes the research progress in this field utilizing paper, understanding fundamental properties w.r.t application, performance enhancement w.r.t material advancements (i.e. paper modification), and technological trends, which is otherwise not yet reviewed earlier. It further sheds light upon the perspectives for their associated and allied technological developments in the energy sector. Graphical Abstract: ga1 Highlights: Role of paper properties in energy related applications are discussed. Paper based electrodes for energy harvesting and conversion devices. Utilty of papers in energy storage i.e. supercapacitors and batteries is presented. Challenges and perspectives of realization of paper based devices for energy sector are projected.